PRESIDENTIAL THRESHOLD TERHADAP PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN REPUBLIK INDONESIA DALAM SISTEM KETATANEGARAAN - Putri Lina Wahyuni; Elidar Sari; Mukhlis M (Fakultas Hukum Universitas Malikussaleh, 2018)
The holding of elections simultaneously raises implications for the mechanism of general elections the President and Vice-President, especially in terms of the implementation of the presidential threshold. After the decision of the Constitutional Court (MK) number 14/PUUXI/2013, which mandates the simultaneous elections raises the pros and cons about setting the presidential threshold. In the perspective of the Constitution, using or not using the presidential threshold indeed does not conflict with the Constitution, because the presidential threshold is the policy of the law that are open from forming laws. The purpose of this paper is to study the presidential threshold in conjunction with a Simultaneous Election in 2019. The method of approach in this research is normative juridical with examines the problems that arise in terms of the law. The presidential threshold has been twice used in the election, the results show evidence that the presidential threshold is very positive become a tool of initial selection of candidates for President and Vice-President. The use of the presidential threshold in the elections in Indonesia was initially set in the 1945 Constitution (UUD 1945) stated in article 6A, and then further regulated in Legislation Number 23/2003 about General Election of President and Vice-President, then amended by Lagislation Number 42/2008 on General Election of President and Vice-President are next rearranged in Lagislation Number 7/2017 about General Elections. In the implementation of the presidential threshold is not necessarily only a positive impact, but there are also negative impacts such as the presence of new parties that have passed verification and are expressed as participants of the election by the Election Commission (KPU) in 2019 it does not have political rights in candidates for President and Vice-President, and the presence of Indonesian citizens who feel maimed political rights for which he choose in the 2014 election not necessarily be the choice in the elections 2019 or the candidate would they choose is canceled forward because the rules of the presidentila threshold. With keep the enactment of the rule threshold in the 2019 elections expected legislators to rethink about the terms of the presidential threshold, especially in conjunction with simultaneous elections, taking into account the advantages and disadvantages in the application or removal of the presidential threshold, for the purpose to strengthen the presidential system in Indonesia. Keywords :The Presidential Threshold, the verdict of the Constitutional Court, Simultaneous Elections